Psychosocial and sexual health factors of Spanish women who participate in ecofeminist spirituality - Santamaría-Dávila, J. (Journal of spirituality in mental health, 2018)
This article explores the spiritual movements emerging from ecofeminism as possible environments where psychosocial and sexual factors are promoted for the Spanish women who participate in them. The study is based on a qualitative exploratory research using the semi-structured interview method. Twelve women between the ages of 33 and 52 were interviewed, all of whom ascribe to this diverse model of spirituality. Data were analyzed using grounded theory. Results reveal that in these ecofeminist spiritual environments, some mental health factors are promoted. Considering these results, some ecofeminist spiritual movements may be acting as community health agents for Spanish women.